Comparison of the mandibular retromolar space in adults with different sagittal skeletal types and eruption patterns of the mandibular third-molar: a cone-beam computed tomography study - Qianya Gao; Xiaohui Zhou; Zuodong Zhao; Baoyi Chen; Min Huang; Huiyi Lin; Weiqi Guo; Chang Liu (BMC, 2024)
Abstract Background The mandibular retromolar space (RMS) has not been extensively studied in relation to various sagittal skeletal classes and patterns of third-molar eruption. The objective of this study was to test the null hypothesis that there is no difference in the mandibular RMS among normodivergent subjects with different skeletal classes and patterns of mandibular third-molar eruption, using cone-beam computed tomography (CBCT). Method A total of 105 normodivergent patients (20-40 years) were included in this study. Participants were categorized into Class I, II and III groups based on ANB and further impacted and erupted groups based on the eruption patterns of the mandibular third molars. Measurements of the mandibular RMS were taken at four planes parallel to the occlusal plane, along the cusp line. Comparative analyses were conducted among the three sagittal groups and between the impacted and erupted groups. Results The Class II group exhibited a statistically smaller RMS (P < 0.05). RMS was found to be larger in third-molar erupted group (P < 0.05). The rates of root contact and third-molar impaction was significantly higher in Class II group. (P < 0.05) Conclusions The null hypothesis was rejected. Patients with Skeletal Class II tend to have a smaller mandibular RMS and a higher prevalence of root contact and third-molar impaction. The presence of impacted mandibular third molars was correlated with a shorter RMS. Trial registration Retrospectively registered.